A report of an unusual case of pediatric eosinophilia associated with platelet-derived growth factor receptor-beta rearrangement - Abdul Wajid Moothedath; Debasish Sahoo; Rachna Seth; Jagdish Prasad Meena; Aditya Kumar Gupta (Indian Journal of Medical and Paediatric Oncology)
Eosinophilia is a common finding in the pediatric age group. While the majority of mild eosinophilia cases are benign and due to reactive causes, persistent hypereosinophilia is uncommon and requires prompt clinical evaluation because of the potential risk of end-organ damage associated with it. Given the broad differential diagnoses of eosinophilia, it is essential to have a systematic approach to the evaluation of unexplained eosinophilia in children. Here, we discuss the case of a 2-year-old child who presented with very high eosinophil counts. A systematic workup of the case helped us in arriving at a rare diagnosis of platelet-derived growth factor receptor-beta (PDGFRB)-rearranged clonal eosinophilia. Identification of such an entity is important as it has therapeutic implications, and early recognition helps in preventing associated end-organ damage by instituting appropriate therapy. Such cases of eosinophilia associated with platelet-derived growth factor receptor-alpha and PDGFRB rearrangement respond dramatically to imatinib.